Pengaruh Perbedaan Kondisi Hidrolisis Terhadap Hasil Isolasi Nanokristalin Selulosa Dari Bonggol Jagung - Purwanti, Endah; Dampang, Sarah (Jurusan Kimia, Fakultas Sains dan Teknologi, Universitas Pattimura, 2017)
Cellulose is one of the largest components in corncobs. Cellulose was obtained from corncob in this research that has a yield of 19.6% of 20 grams of corncob powder. The isolated cellulose was characterized by using FTIR and SEM. Cellulose has crystalline chain and insoluble in water or organic solvents. The molecular chain of cellulose is linear and has intra- and inter-molecular hydrogen bonds. One way for cellulose to be easy in the treatment of applications, is to convert microcrystalline cellulose into nanocrystalline cellulose. Nanocrystalline cellulose can be obtained by several methods, one of them by acid hydrolysis. Hydrolysis of cellulose by using sulfuric acid produces nanocrystalline cellulose. Nanocrystalline cellulose can be characterized by using TEM and PSA analysis. CNC 60 has a particle size distribution with a diameter range of 14.3 nm - 45.0 nm and an average diameter of 17.4 nm. Whereas cellulose with CNC 90 has a smaller particle size distribution with a diameter range of 10.0 nm - 17.1 nm and an average diameter of 11.9 nm.